2006
DOI: 10.1159/000107773
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Stained Nucleolar Organizer Regions in Normal and Dysplastic Cervical Lesions: Correlation with DNA Ploidy and S-Phase Fraction by Flow Cytometry

Abstract: Objectives: To investigate the prognostic significance of DNA ploidy and silver-stained nucleolar organizer regions (AgNOR), their relation to the cytological grades of cervical dysplasia and correlation of cells in the S-phase of the cell cycle and DNA ploidy with AgNOR count. Methods: Multiparametric DNA flow-cytometric analysis and AgNOR count were performed on cervical smear samples, cytologically diagnosed as normal (n = 196), atypical squamous cells of unknown significance (ASCUS, n = 98) and various gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Atypical polymorphism showed a significant increase in patients with LSIL, HSIL and SCC. This increase may be explained by the relationship between morphological changes in the AgNORs and high transcriptional activity due to proliferative potential, increased activity of rRNA genes, ploidy and aneuploid DNA 15,39 or infection of the cells with HPV. 40 In this work, all samples were infected with high-risk HPV types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical polymorphism showed a significant increase in patients with LSIL, HSIL and SCC. This increase may be explained by the relationship between morphological changes in the AgNORs and high transcriptional activity due to proliferative potential, increased activity of rRNA genes, ploidy and aneuploid DNA 15,39 or infection of the cells with HPV. 40 In this work, all samples were infected with high-risk HPV types.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] It has also been shown that high AgNOR count, 14 S-phase fraction and aneuploid DNA have prognostic significance in the early detection of cervical cancer. 15 However, at present it has also been described that the increase in polymorphism of AgNORs in cervical biopsies could be used as a possible marker for histopathological diagnosis. 16,17 Furthermore, only a few reports have been published concerning the variability of AgNORs in cervical cytology in women with cervical neoplastic damage, suggesting that polymorphism of AgNORs may be related to neoplastic development.…”
Section: Introductionmentioning
confidence: 99%
“…Usually 10,000 nuclei were counted and DNA ploidy was expressedby the DI. The DI was calculated according to the principles recommended by consensus (5). DI representsthe ratio of the aneuploid G 1 -G 0 -DNA peak channel to the diploid G 1 -G 0 -DNA peak channel.…”
Section: Methodsmentioning
confidence: 99%
“…Results demonstrated a progressive increase in AgNOR counts when the severity of the lesions increased, mainly in the differentiation between low and high-grade SIL. In addition, on [20] and [21] they analyzed the AgNOR count as a marker of malignancy progression. As the count shows the intensity of cell proliferation, this method can be used in differentiating between low and high degree of cervical dysplasia, as well as between lesions with high and low potential for malignant transformation.…”
Section: Related Workmentioning
confidence: 99%